2014
DOI: 10.5194/acp-14-1141-2014
|View full text |Cite
|
Sign up to set email alerts
|

Satellite observations of cloud regime development: the role of aerosol processes

Abstract: Abstract. Many different interactions between aerosols and clouds have been postulated, based on correlations between satellite retrieved aerosol and cloud properties. Previous studies highlighted the importance of meteorological covariations to the observed correlations.In this work, we make use of multiple temporally-spaced satellite retrievals to observe the development of cloud regimes. The observation of cloud regime development allows us to account for the influences of cloud fraction (CF) and meteorolog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
85
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 60 publications
3
85
1
Order By: Relevance
“…LTS is defined as the difference in potential temperature between the free troposphere (700 hpa) and the surface, which is representative of typical thermodynamic conditions (Klein and Hartmanm, 1993). It has been suggested that relative humidity, LTS and PVV affect aerosol and cloud interaction (Gryspeerdt et al, 2014;Small et al, 2011). A positive LTS is associated with a stable atmosphere in which vertical mixing is prohibited; negative PVV indicates a local upward motion of air parcels.…”
Section: Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…LTS is defined as the difference in potential temperature between the free troposphere (700 hpa) and the surface, which is representative of typical thermodynamic conditions (Klein and Hartmanm, 1993). It has been suggested that relative humidity, LTS and PVV affect aerosol and cloud interaction (Gryspeerdt et al, 2014;Small et al, 2011). A positive LTS is associated with a stable atmosphere in which vertical mixing is prohibited; negative PVV indicates a local upward motion of air parcels.…”
Section: Data Processingmentioning
confidence: 99%
“…Impacts of aerosols on clouds and precipitation have been reported as introducing the largest uncertainty in quantifying the anthropogenic contribution to climate change (Rosenfeld, 2000;Twomey, 1974;Gryspeerdt et al, 2014;Kaufman et al, 2012). Atmospheric aerosol particles have been recognized as having two effects on Earth's climate.…”
Section: Introductionmentioning
confidence: 99%
“…Actual clouds may not satisfy the homogeneity assumption (Schutgens and Roebeling, 2009). Moreover, the coarse resolution limits the usage in certain aerosol-cloud interaction studies (Sekiguchi, 2003;Gryspeerdt et al, 2014). Based on the above analysis, the following two questions are the focal points of this study.…”
Section: Introductionmentioning
confidence: 99%
“…CC BY 4.0 License. (Williams and Webb, 2009;Gryspeerdt et al, 2014). Being based purely on the observed cloud properties, "cloud regimes" do not require assumptions about the impact of local meteorology on the regime occurrence.…”
mentioning
confidence: 99%